The impact of ESG initiatives on green product and consumer purchase intentions - Choi , Yoon Qi (2024)
Environmental, Social, and Governance (ESG) initiatives are critical determinants of consumer purchase intentions, particularly in the context of green products. With the rising global and local emphasis on sustainability, it is imperative for companies to implement robust ESG strategies to stand out in the competitive market and foster consumer trust. The purpose of this research is to investigate the impact of ESG components such as environmental, social, and governance on green trust and their influence on consumer purchase intentions. An online survey using a structured questionnaire was distributed to 260 Malaysian consumers familiar with green products. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 30 Results indicate a positive relationship between all three ESG components and green trust, which in turn significantly impacts purchase intentions. Additionally, the mediating role of Green Trust was tested using the Sobel test, and the results show a positive and significant relationship between ESG components and consumer purchase intentions. The implications of the study were discussed for the public, companies, and governance, providing insights into practical implications and theoretical implications. The research also addressed its limitations and provided recommendations for future studies to enhance and expand upon the findings when researching the same topic.